Business plan and its contribution to sustainable tourism development in the destination Sucre – San Vicente - Zambrano Zambrano, Moisés David (2025)
Context: Business bread currently plays a leading role in ventures. Objective: develop a diagnosis in commercial activity to verify the prevalence of business plans and their contribution to the tourism sustainability of the Sucre-San Vicente destination. Method: The research is quantitative and was based on statistical figures obtained from the Extension Tourism Observatory. The explanatory analytical method sought to determine the main causes and effects that have generated the absence of business plans in the different tourist facilities in the sector under study. The population represented by 51 gastronomic infrastructures, 70 commerce and shops and 39 fashion and beauty establishments representing 50.3% of the total services considering a simple non-probabilistic random sampling. Results: A questionnaire of 10 questions was applied on the Likert scale where it was observed that 92.7% of these businesses were conceived without the implementation of a business plan and where 69.2% do not show interest in developing it, although 84.6% recognize that tourism activity is the alternative to achieve economic indicators at the level of representative and sustainable destinations. Conclusion: These results show instabilities in the services, ignoring their sales projections and their scope.